Simulating Machines: Modelling, Metaphysics and the Mechanosphere. - Shults, F. LeRon (Deleuze & Guattari Studies, 2020)
This article explores some of the ways in which the conceptual apparatus of A Thousand Plateaus, and especially its machinic metaphysics, can be connected to recent developments in computer modelling and social simulation, which provide new tools for thinking that are becoming increasingly popular among philosophers and social scientists. Conversely, the successful deployment of these tools provides warrant for the flat ontology articulated in A Thousand Plateaus and therefore contributes to the 'reversal of Platonism' for which Deleuze had called in his earlier works, such as Logic of Sense. The first major section offers a brief exposition of some key concepts in A Thousand Plateaus in order to set the stage for the second and third major sections, which argue that the fabrication of a metaphysics of immanence can be accelerated by connecting its conceptual apparatus more explicitly to insights derived from philosophical analyses of computational modelling and simulation and the social scientific use of 'assemblage theory'. The article concludes with a summary of the argument and a brief consideration of some of the potential ethical and political implications of this interdisciplinary engagement.